Sourcing in an Increasingly Expensive China: Four Swedish Cases - Fang, Tony; Gunterberg, Caroline; Larsson, Emma (2010)
China has long enjoyed its position as the world’s cheapest production country. However, this position is being shaken due to the increasingly rising costs in China in pace with China’s rapid economic development. China’s New Labour Contract Law which took effect from 1 January 2008 has further pushed the labour costs in China in general. The purpose of this article is to arrive at an in-depth understanding of why foreign firms conduct sourcing in China where sourcing is becoming increasingly expensive. The experiences of four Swedish companies in the textile and clothing industry (TCI) conducting sourcing in China are presented. Our findings show that sourcing in China is becoming both cost- and strategy-driven. Companies purely chasing the cheapest production would most probably consider leaving China, whereas companies with a long-term strategic intent and a high level of business ethics and corporate social responsibility (CSR) practices will retain all or most of their sourcing activities on the Chinese soil despite the rising costs.
Keywords: textile and clothing industry (TCI); Swedish companies; Price; Manufacturing; sourcing; CSR; China